Comparing digital libraries in the web and mobile contexts from the perspective of the digital divide. (December 2015) - Zha, Xianjin; Zhang, Jinchao; Yan, Yalan
Building on concepts of the digital divide, this study explores and compares users' perceptions of web digital libraries and mobile digital libraries in terms of ease of use and usefulness. Data collected from 306 university library users were analyzed. Two figures were used to present the exact nature of users' perceptions of ease of use and usefulness in terms of data distribution. These figures were supplemented by the paired samples t test which presents the exact mean difference between web digital libraries and mobile digital libraries in terms of ease of use and usefulness. The data distribution suggests that there are more users who think digital libraries are both easy to use and useful whereas mobile digital libraries are neither easy to use nor useful. The mean comparison of ease of use and usefulness shows that web digital libraries significantly exceed mobile digital libraries. These findings and implications are discussed.